2018
DOI: 10.1080/03008207.2018.1439483
|View full text |Cite
|
Sign up to set email alerts
|

TGF-b1 or hypoxia enhance glucose metabolism and lactate production via HIF1A signaling in tendon cells

Abstract: We discuss the likely outcome of this major metabolic shift in terms of the potential benefits and damage to tendon and suggest how incorporation of this metabolic response into our understanding of initiation and progression of tendinopathies may offer new opportunities for diagnosis and the monitoring of therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
(67 reference statements)
3
29
0
Order By: Relevance
“…The current results showed that, similar to our intra‐tendinous TGFβ1 injury model, TGFβ1 injection into the RCB induced rapid and pathologic formation of an inflammatory tendon matrix, rich in HA and CS/DS (Figs. –).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The current results showed that, similar to our intra‐tendinous TGFβ1 injury model, TGFβ1 injection into the RCB induced rapid and pathologic formation of an inflammatory tendon matrix, rich in HA and CS/DS (Figs. –).…”
Section: Discussionsupporting
confidence: 82%
“…In the clinical setting, retrocalcaneal bursitis is routinely treated with either corticosteroid injection, non‐steroidal anti‐inflammatory drug (NSAIDs) administration or activity modification, all directed to managing tendinopathies to protect the tendon from long‐term irreversible damage . However, anti‐inflammatory drugs for tendinopathy show poor long‐term outcomes, and the limited surgical options involve significant compliance during recovery, a requirement that is often difficult for patients to adhere to, and inadequate healing or wound complications can lead to morbidity of the tissue …”
mentioning
confidence: 99%
“…RNA was isolated from the intact tissue (following fragmentation in a Bessman tissue pulverizer at − 196°C) and from MSCs [passage 2 (P2)] via TRIzol® extraction (Invitrogen, Grand Island, NY) as previously described [4,20,33]. Briefly, RNA was purified with an RNeasy MiniKit (Qiagen, Valencia, CA) with RNA concentration and purity (A260/280 > 1.9) analyzed using a Nanodrop (ND-1000, Thermoscientific Waltham, MA).…”
Section: Quantitative Real Time Pcrmentioning
confidence: 99%
“…Existing models were also used to evaluate cross talk within tendon to systemic disease (6) and to induction of tendon cell stress in localized tendinopathy (7). At first look the findings of these two studies appear to be unrelated, but an intriguing connection emerges on closer inspection.…”
Section: Multiscale Molecular Interactions Of Tendonmentioning
confidence: 99%
“…Using their recently described TGFβ1 injection model of Achilles tendinopathy to examine HIF1A mediated glucose metabolism and lactate production in both Adamts5-deficient and wild-type mice, Sikes et al (7) demonstrate that metabolic reprogramming of the glycolytic pathway and increased lactate production via activation of the Warburg pathway is a critical part of the cellular stress response of tendons to injury. The data agree with previously reported increases in lactate in painful chronic Achilles tendinopathy and provide a potential novel metabolic biomarker of tendinopathy.…”
Section: Multiscale Molecular Interactions Of Tendonmentioning
confidence: 99%